Taking Account of Nonlinear Properties of Subsystems in Problems of Dynamic Interaction of Structures with Loads, Bases and Flows - Kulyabko, Vladimir; Chaban, Vyacheslav; Makarov, Andrey; Yaroshenko, Denis (NTU "KhPI", 2016)
This paper describes the additional features of discrete models of various DOF systems to solve nonlinear dynamical problems of complex-compound buildings and structures including elements of significant flexibility (bridges, pylons and supports of power transmission lines, pipe line crossings, guyed masts etc.). Qualitative and quantitative differences between linear solutions (which are popular among FEM designers) and nonlinear solutions (depending on geometrical, physical and constructive nonlinearities) are discussed. It is analyzed the time-history models of different combinations of mention structures with the adjacent subsystems, damping devices (well-known and the most-recently-used), static and dynamic loads and effects (including moving loads). There is also presented experimental and theoretical approach of damages determination for rod elements in the spatial structure by the dynamic diagnosis method (e.g. for bridges crane with the big span).
Keywords: nonlinear structural dynamics; modelling; geometrical; physical and constructive nonlinearities; damping; tuned mass damper; diagnosis of damage